Ukrainian youth morbidity / Disability in the focus of the Council of Europe strategy on the rights of people with disabilities for 2017-2023 - Honchar, Yuliia Aleksandrovna; Khramtsova, Victoriia Viktorovna (Social Welfare: Interdisciplinary Approach, 2019)
The dynamics of morbidity and prevalence of diseases among the children’s population in Ukraine in recent years has multi-directional trends – an increase in the incidence and prevalence of diseases among children 7-14 years and adolescent children, and the reduction of the morbidity of children of the first year of life, the incidence and prevalence of diseases among children 0- 6 years. The decrease of the morbidity and increase of the prevalence of diseases with age was revealed. At the beginning of the 21st century, the problem of maternal and child health has become one of the priorities of public health protection in the world and was included by the United Nations in the Millennium Development Goals List. Ukraine is designated by the WHO European Regional Committee as a pilot region for the implementation of the Strategy “Health and Development of Children and Adolescents”. A data on children with disabilities in Ukraine are rare and do not give a general idea of the link between morbidity and disability, and because that information is available only by regions, not nosological forms, it can not provide a general picture of morbidity/ disability of young people in order to develop organizational measures to reduce that. The general objective of the Council of Europe Strategy for the Rights of Persons with Disabilities for 2017-2023 is to "shift the paradigm" from the traditional medical approach to disability to a human rights-based approach: independence, freedom of choice, full participation, equality, human dignity and equal opportunities for persons with disabilities. The effective participation of people with disabilities in all spheres of life and society as a whole is crucial for the realization of all human rights and the formation of their life perspective in Ukraine.